1998
DOI: 10.1007/s003840050156
|View full text |Cite
|
Sign up to set email alerts
|

Rubber band ligation of hemorrhoids: relapse as a function of time

Abstract: Rubber band ligation is a well established treatment of internal second-degree hemorrhoids. Up to now, the long-term results (> 5 years) of this method have not been assessed. The aim of this study was to determine the long-term success rate of rubber band ligation in patients with a first episode of second-degree hemorrhoids not responding to medical treatment (local cream with laxative). A total of 92 patients who were treated between 1979 and 1997 for second-degree hemorrhoids responded to a questionnaire. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 0 publications
0
17
0
2
Order By: Relevance
“…We chose to analyze this phenomenon using a KaplanMeier survival curve (Fig. 2) with similar results to those of Savioz et al 15 This relationship between follow-up time and recurrence also is shown by Konings et al 13 Wrobleski et al 16 in a minimum follow-up of 36 (mean, 60) months reported 80 percent improvement with 69 percent totally symptom-free and a subsequent hemorrhoidectomy rate of 7.5 percent. Lau et al 17 reported a subsequent hemorrhoidectomy rate of 3 percent.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We chose to analyze this phenomenon using a KaplanMeier survival curve (Fig. 2) with similar results to those of Savioz et al 15 This relationship between follow-up time and recurrence also is shown by Konings et al 13 Wrobleski et al 16 in a minimum follow-up of 36 (mean, 60) months reported 80 percent improvement with 69 percent totally symptom-free and a subsequent hemorrhoidectomy rate of 7.5 percent. Lau et al 17 reported a subsequent hemorrhoidectomy rate of 3 percent.…”
Section: Discussionmentioning
confidence: 85%
“…[6][7][8][9][10] There have been a few studies analyzing the longterm effectiveness of RBL as an initial treatment for symptomatic internal hemorrhoids. [12][13][14][15][16] We examined the long-term outcomes in this retrospective analysis of 2,114 rubber band ligations in 805 patients. As part of our analysis, we explored whether the number of bands placed and hemorrhoidal grade might predict a successful outcome.…”
mentioning
confidence: 99%
“…The first one, in particular, became popular for its goods results and low complication rates in seconddegree symptomatic piles [7]. The main disadvantages of these outpatient procedures are the requirement for several treatment sessions and the high recurrence rates [8,9].…”
Section: Pp Dal Monte • C Tagariello • P Giordano • E Cudazzo • mentioning
confidence: 99%
“…However, a review of the literature on excisional hemorrhoidectomy and other traditional methods revealed that, although early recurrence is typically rare, there is a significant rate of late recurrence, which increases with the length of follow-up [2,12,16,19]. Arbman et al [2] reported a 10% recurrence of prolapsing hemorrhoids 1 year after excisional hemorrhoidectomy, and Konsten and Baeten [12] found a 26% recurrence at 17 years after surgery.…”
Section: Discussionmentioning
confidence: 99%